Wahhabism and the world: understanding Saudi Arabia's global influence on Islam - Mandaville, Peter G. (Religion and global politics series, 2022)
For more than half a century, Saudi Arabia - through both official and non-governmental channels - has poured billions of dollars into funding and sponsoring religious activities and Islamic causes around the world. The effect has been to propagate Wahhabism, the distinctively rigid and austere form of Islam associated with the Kingdom's religious establishment, within Muslim communities on almost every continent. This volume features essays by leading scholars who explore the origins and evolution of Saudi religious transnationalism, assess ongoing debates about the impact of these influences in various regions and localities around the world, and discuss possible future trends in light of new Saudi leadership